2004
DOI: 10.1097/00005537-200404000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Laryngopharyngeal Reflux on Patient‐Reported Quality of Life

Abstract: The study's assessment of health-related quality of life suggests that laryngopharyngeal reflux has a significant negative impact on the lives of patients. Although its impact is similar in some respects to that of gastroesophageal reflux disease, laryngopharyngeal reflux has a more significant impact on patients' social functioning and vitality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 29 publications
(23 reference statements)
5
54
0
2
Order By: Relevance
“…The scores in our study were in the same range as found in previous studies describing patients suffering from posterior laryngitis, and confirm that these patients have a reduced HRQOL [26][27][28]. The new finding in the present study is that the reduced scores apply to the female population and not to the male population.…”
Section: Discussionsupporting
confidence: 90%
“…The scores in our study were in the same range as found in previous studies describing patients suffering from posterior laryngitis, and confirm that these patients have a reduced HRQOL [26][27][28]. The new finding in the present study is that the reduced scores apply to the female population and not to the male population.…”
Section: Discussionsupporting
confidence: 90%
“…The most frequent activities of daily living were impaired in nearly 20% of the subjects [29]. The presence of extra-oesophageal signs of GERD such as "globus", hoarseness, and throat clearing may also be reflected by diminished quality of life, particularly with regards to vitality and social contacts [30]. A systematic review of literature conducted by Gerson and Fass suggests that dyspeptic symptoms are common in patients with GERD and impact their HRQOL [31].…”
Section: Quality Of Life In Patients With Gastroesophageal Reflux Dismentioning
confidence: 99%
“…Chorzy, u których rozpoznano pozaprzełykowe objawy GERD odznaczali się gorszą jakością życia niż osoby mają-ce klasyczne objawy. Różnica ta była szczególnie widoczna w sferze kontaktów międzyludzkich i na poziomie witalności [17].…”
Section: Objawy Występujące W Przebiegu Choroby Refluksowej Przełykuunclassified